Recurrent intussusception as a rare clinical manifestation of intestinal malrotation in children-a case report and review of literature - Aditya Arvind Manekar; Narahari Janjala; Subrat Kumar Sahoo; Bikasha Bihary Tripathy; Manoj Kumar Mohanty (SpringerOpen, 2021)
Abstract Background Mobile caecum along with malfixed small bowel mesentery in malrotation is incriminated to cause intussusception in children. This dual association is very rare and is labeled as Waugh's syndrome. This is often missed during conservative management of intussusception and may manifest as chronic intussusception. Case presentation We report a rare case of intestinal malrotation in a 13-year-old boy who presented as recurrent intussusception. The child was resuscitated and was operated, where malrotation of gut was detected. We discuss the clinical presentation, radiological findings, and management of this rare association in light of current available literature. Conclusion The presence of mobile caecum and redundant bowel loops with narrow mesentery in case of malrotation is an important factor leading to intussusception.